The role of hydrodynamic forcing, sediment transport processes and bottom substratum in the shoreward development of Posidonia oceanica meadow. (15th November 2018) - Ruju, Andrea; Ibba, Angelo; Porta, Marco; Buosi, Carla; Passarella, Marinella; De Muro, Sandro
Abstract: This paper investigates the combined role of hydrodynamic forcing, sediment transport processes and sea bottom features in determining the location of the meadow upper limit of the endemic Mediterranean seagrass Posidonia oceanica . For this purpose, an approach including extreme wave analysis and numerical modelling is applied to two sandy beach systems located in southern Sardinia (Italy). Information about bathymetry, P. oceanica meadow extension and bottom features has been made available by previous published studies. Based on the 30-year long NOAA hindcast dataset, a wave climate analysis is carried out to identify the incoming storm wave conditions (1 year return period) to be simulated with the Delft3D model package. The simulation results extend the current knowledge highlighting the importance of wave-induced hydrodynamic parameters as limiting factors for the survival of P. oceanica meadows. In particular, the results suggest that on sandy substrata the meadow upper limit lies well offshore of the surf zone, in areas with little morphological activity, where the wave orbital velocities associated to storms are on the order of 0.8 m/s and the mean current magnitude does not exceed 0.5 m/s. On rocky bottoms, the P. oceanica meadow can extend up to the outer surf zone of storms and is thus able to colonize shallow areas subject to stronger hydrodynamic forcings than those observed on sand. This difference in the plant tolerance to wave forcing depending on the substratum type shows how both hydrodynamic and geological factors play a key role in defining the environmental conditions for the development of seagrass meadows.